Interdomain multicast routing : practical Juniper Networks and Cisco systems solutions - Edwards, Brian M. (Addison-Wesley, 2002)
IP multicast is rapidly coming of age: its principles are solid, its protocols are being finalized, and it is increasingly being implemented in real-world ISP and enterprise networks. Now, a team of Juniper Networks IP multicast experts have written the most authoritative and up-to-date guide to IP multicast implementation. This book covers everything network professionals must know about IP multicast protocols, applications, network design and integration, deployment, configuration, and management. The authors, who support many of the world's largest networks, also offer never-before-published solutions to the key challenges and pitfalls encountered by early implementers. They review the goals and fundamental principles, then introduce all new IP multicast protocols, including DVMRP, PIM-DM, PIM-SM, MSDP, multiprotocol extensions to BGP; SSM, M-ISIS, and more. Next, they demonstrate the configuration of Internet -based multicasting on both Juniper and Cisco routers; and present a detailed case study. For network engineers and designers; network backbone engineers; technical leaders at ISPs and large enterprise networks; and network professionals connecting to backbones that support IP multicast.